2022
DOI: 10.1186/s12882-022-02818-3
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of inappropriate antidiuretic hormone secretion is associated with different proton pump inhibitor use: a pharmacovigilance study

Abstract: Aim The objective of this study was to evaluate the reported associations between the syndrome of inappropriate antidiuretic hormone secretion (SIADH) and a variety of proton pump inhibitors (PPI) through analysis of the reports extracted from the Food and Drug Administration Adverse Event Reporting System (FAERS). Methods FAERS reports from January 2004 to March 2020 were used to conduct disproportionality and Bayesian analyses. The definition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Several gender differences in the adverse reactions to PPIs have been reported. A recent study in China demonstrated that women were more likely to develop the PPI-related syndrome of inappropriate antidiuretic secretion (SIADH) [86]. However, the risk of PPI-associated hypomagnesemia was higher in males and in the elderly population [85].…”
Section: Other Side Effects Of Ppismentioning
confidence: 99%
“…Several gender differences in the adverse reactions to PPIs have been reported. A recent study in China demonstrated that women were more likely to develop the PPI-related syndrome of inappropriate antidiuretic secretion (SIADH) [86]. However, the risk of PPI-associated hypomagnesemia was higher in males and in the elderly population [85].…”
Section: Other Side Effects Of Ppismentioning
confidence: 99%